Does Tagline have an impact towards Purchase Intention? - Triadinda, Dexi; Savitri, Citra; Rozak, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
JD.ID conducted a campaign with the tagline "Dijamin Ori" because they consider that there are still many e-commerce sites that sell non-original products. There are several types of products that are often falsified so as to encourage the JD, ID to use these strategies to attract consumer buying interest. In addition, JD.ID also markets its online business platform via the YouTube site which is one of the video-based marketing media. This study aims to analyze the effectiveness of the "Dijamin Ori" Tagline and JD.ID Youtube Ads on consumer buying interest. This analysis uses independent variables namely the tagline "Dijamin Ori" and Youtube Ads. The dependent variable is Consumer Purchase Interest. This type of research used in this research is explanatory research, the research used to explain the causal relationship between variables through hypothesis testing that was formulated, with survey methods and the number of samples in this study were 110 respondents. The sampling technique was obtained using the Accidental Sampling method. Data sources using primary data and using secondary data, namely literature and from the internet. While the data analysis technique used in this study is a quantitative analysis using analysis through the help of the SPSS program, namely: Multiple Linear Regression Analysis.